José Chasin, «Marx. Ontologia e metodo»: traduzione e cura di Marco Vanzulli, presentazione di Ester Vaisman e Antônio José Lopes Alves, Milano, Mimesis, 2010, XVIII-232 pp., 17,00 Euro (ISBN 978-88-5750-111-6) - Sgro’, Giovanni (Quaderni Materialisti, 2011)